2015
DOI: 10.7554/elife.06306
|View full text |Cite
|
Sign up to set email alerts
|

dPob/EMC is essential for biosynthesis of rhodopsin and other multi-pass membrane proteins in Drosophila photoreceptors

Abstract: In eukaryotes, most integral membrane proteins are synthesized, integrated into the membrane, and folded properly in the endoplasmic reticulum (ER). We screened the mutants affecting rhabdomeric expression of rhodopsin 1 (Rh1) in the Drosophila photoreceptors and found that dPob/EMC3, EMC1, and EMC8/9, Drosophila homologs of subunits of ER membrane protein complex (EMC), are essential for stabilization of immature Rh1 in an earlier step than that at which another Rh1-specific chaperone (NinaA) acts. dPob/EMC3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
130
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(149 citation statements)
references
References 45 publications
(65 reference statements)
8
130
1
Order By: Relevance
“…In Saccharomyces cerevisiae, deletion of Emc1-6 activated the sensor of misfolded proteins, Ire1p, and induced Hac1p splicing and the UPR (8). In Drosophila, loss of Emc3 in the retina activated IreI/Xbp1 and eIF2α phosphorylation (12). Consistent with those findings, we found that deletion of Emc3 in AT2 cells activated 2 of the 3 branches of the UPR, including IRE1α/XBP1 and PERK/eIF2α, as indicated by XBP1 and ATF4 activities, respectively.…”
Section: Tm1a(eucomm)wtsisupporting
confidence: 78%
See 2 more Smart Citations
“…In Saccharomyces cerevisiae, deletion of Emc1-6 activated the sensor of misfolded proteins, Ire1p, and induced Hac1p splicing and the UPR (8). In Drosophila, loss of Emc3 in the retina activated IreI/Xbp1 and eIF2α phosphorylation (12). Consistent with those findings, we found that deletion of Emc3 in AT2 cells activated 2 of the 3 branches of the UPR, including IRE1α/XBP1 and PERK/eIF2α, as indicated by XBP1 and ATF4 activities, respectively.…”
Section: Tm1a(eucomm)wtsisupporting
confidence: 78%
“…Work in Danio (13), Caenorhabditis elegans (10, 11), and Drosophila (12) demonstrated that EMCs are critical for the biogenesis of multipass transmembrane proteins, but not for secreted proteins or type I single-pass transmembrane proteins. Consistent with these findings, our data demonstrated that EMC3 and other EMC subunits directly bound to and stabilized ABCA3, a 12-pass transmembrane protein (Figure 4).…”
Section: Tm1a(eucomm)wtsimentioning
confidence: 99%
See 1 more Smart Citation
“…The EMC is needed for transmembrane protein folding (Jonikas et al, 2009) and has been implicated in regulating the expression of the rhodopsin receptor in flies (Satoh et al, 2015) as well as orchestrating the transfer of lipids from the ER to the mitochondria in yeast (Lahiri et al, 2014). Notably, a pooled CRISPR/Cas9 screen for WNV host factors found three components of the EMC to be needed for WNVinduced cell death but not for viral replication (Ma et al, 2015).…”
Section: Denv-hf Pathways and Complexesmentioning
confidence: 97%
“…It has also been shown that the EMC is an ER-mitochondria tether in S. cerevisiae that interacts with the outer membrane protein Tom5 of the TOM (Translocase of the Mitochondrial Outer Membrane) complex ( Lahiri et al , 2014). Most recently, the EMC has been implicated in the proper assembly of multi-pass transmembrane (TM) proteins ( Satoh et al , 2015). These recent findings suggest that EMC involvement in ERAD may be due to secondary effects, as cells devoid of EMC components may result in either disruption of ER-mitochondria tethering, or the misfolding of multipass membrane proteins.…”
Section: Introductionmentioning
confidence: 99%